Impact of real-time continuous glucose monitoring on glycaemic control in adults with type 2 diabetes: systematic review and meta-analysis - Lian, Xia; Cheng, Ling Jie; Teo, Claire Jun Yi; Tan, Isaac Jun Song; Lim, Helen; Shen, Liang; Chew, Jocelyn Han Shi; Wang, Wenru; Dalan, Rinkoo (Frontiers in Endocrinology, 2026)
ObjectiveTo evaluate the effectiveness of real-time continuous glucose monitoring compared with self-monitoring of blood glucose in adults with type 2 diabetes, focusing on glycaemic control, cardiometabolic outcomes, and patient-centred measures.MethodsRandomised controlled trials published in English with study intervention period ≥12 weeks, which compared real-time continuous glucose monitoring with self-monitoring of blood glucose in adults with type 2 diabetes were included in this systematic review. Analyses were conducted using Review Manager version 9.6. Risk of bias was evaluated using the Cochrane risk-of-bias tool. The Grading of Recommendations Assessment, Development and Evaluations approach was used to assess certainty of evidence.Data SourcesThe search was conducted across PubMed, CINAHL, Web of Science, the Cochrane Library databases and ClinicalTrials.gov from inception to July 2025.ResultsThis systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Eleven studies which compared real-time continuous glucose monitoring (n=437) with self-monitoring of blood glucose (n=352) were included. Real-time continuous glucose monitoring use was associated with a significant reduction in HbA1c (mean difference=−0.20%), improved time-in-range (mean difference=7.41%), reduced time-above-range (mean difference=6.93%) and reduced time-below-range (mean difference=0.26%). Glucose variability was significantly lower (mean difference=-1.06%) and users demonstrated greater improvements in readiness for diabetes self-management (standardised mean difference=0.69). No significant differences were observed in cardiometabolic or psychosocial outcomes.ConclusionReal-time continuous glucose monitoring improves glycaemic control and self-management capacity compared with self-monitoring of blood glucose in adults with type 2 diabetes. These findings support the integration of real-time continuous glucose monitoring into routine clinical care, particularly for individuals requiring intensive glucose monitoring and tailored self-care support.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025625444.